Microorganisms associated with bacterial vaginosis: diversity and clinical and diagnostic significance - N. M. Voropaeva (Scientific Сentre for Family Health and Human Reproduction Problems, 2021)
Bacterial vaginosis (BV) is the most common infectious non-inflammatory disease in women of reproductive age. The key feature of BV is that in the  absence of a specific pathogen, the disease develops against the background of vaginal biotope dysbiosis. According to the opinion of some authors, initially, the main role of BV in the pathogenesis was assigned to the species G. vaginalis. However, using of molecular methods made it possible to significantly expand the range of microorganisms found in women with BV, and to identify Gardnerella vaginalis, Atopobium vaginae, Mobiluncus spp., Prevotella spp. as the primary causative agents of BV. A number of studies have confirmed the sexual transmission of BV pathogens, with a new sexual partner being significant risk factors for episodic BV, and sexual contact with the same partner without using barrier methods of contraception for recurrent BV. At the same time, BV-associated bacterias  rarely exist as planktonic forms of one species, more often, they thrive in complex polymicrobial communities surrounded by an extracellular matrix, the so-called biofilms. In patients with BV, biofilms are detected in 90% of cases. G. vaginalis and Prevotella bivia are widespread in women with BV and, being the primary colonizers, create a bacterial biofilm, to which secondary colonizers can subsequently join, including A. vaginae, Sneathia spp. and potentially other BVABs. The resistance of bacterias in the biofilm to antimicrobial drugs is 1000 times higher than of planktonic forms, which can lead to chronicity of the infectious process and torpid course of the disease.The aim of this review was analyzing of modern studies on the prevalence, characteristics of opportunistic microorganisms associated with BV, to present their clinical and diagnostic significance and role in the pathogenesis of  diseases.